The relationship between ESG Performance and Financial Stability: are sustainable companies less likely to fail? - Porta, Michela (My University, 2024)
The purpose of this thesis is to study if high ESG performance is related to firm performance, specifically their bankruptcy probability, which is measured by Altman Z-Score in European countries. The sample includes 1740 different companies during the period 2011-2021. Moreover, this thesis aims to study whether there are ESG pillars that impact a firm’s financial performance the most. The importance of corporate sustainability and responsibility has grown in recent decades, driven by factors such as environmental and societal concerns, including climate change and human rights issues, legislative changes, and shifts in public sentiment.. Consequently, companies are trying to improve their way of employing and disclosing sustainability strategies and environmental, social, and governance (ESG) information. This has caused the need for fundamental changes in business models and management. However, previous literature has not come yet to a solid conclusion on whether ESG Performance (ESGP) and corporate financial stability are related or not. Many studies suggest that this relationship is positive, others, on the other end, found a slightly negative correlation or a non-linear link. This thesis aims to investigate if the financial performance of European companies is related to their ESG ratings for the years 2011-2021. The FDR (Financial Distress Risk) is measured with the Altman Z’’-Score, a statistical method used to calculate the probability of firms’ bankruptcy, while the Refinitiv ESG Combined Score is used as a proxy for environmental, social, and governance performance. The results, once again, prove that the link between these two variables is not as simple and linear as one may think. The ESGP-FDR relationship is influenced by numerous factors, and the outcomes appear to be relatively neutral and diverse. Consequently, based on the findings of this thesis, it is challenging to definitively assert whether high ESG scores exert a more positive or negative impact on firms' financial performance in Europe.
Keywords: finance; sustainability reporting; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance